The Quality of Government Financial Reports : Factor’s That Can Affect It - Moch Indra Raharja; Kartika Berliani (eCo-Fin, 2025)
In this study, the standard of the Bandung Regency Health Office's financial reports will be examined in relation pertaining to internal control framework of the government, human resource competency and utilization of official accounting standards. The research approach used is a quantitative one that combines a descriptive and verifying approach. Applying the non-probability sampling method with the Slovin formula, sixty-four individuals from the Bandung district health office were chosen as samples for this study. Descriptive statistics use reliability and validity tests. Regression analysis using multiple linear, determination coefficients, correlation coefficients for product moments and statistical testing for verification uses standard assumptions. A variety of data analysis methods are used like as simultaneous and partial testing (f-test and t-tests). Data is processed using SPSS software. Internal Control System of the Government, Competency in Human Resource and the Implementation of Government Accounting Standards do not affect the quality of financial reports per data from a partial research. However, There isn't any relationship between the quality of financial reports and the Internal Control System of the Government, Competency in Human Resource and the Implementation of Government Accounting Standards according to contemporaneous research findings.